Role of IVRI in Human Resource Development - Rani, Shashi; Prasad, J. K.; Singh, V. P. (Indian Farming, 2015)
The IVRI as Deemed University has envisaged the approaches toaccomplish the set goals and objectives in research by development of rapid and sensitive diagnostic tests and kits for diagnosis of animal diseases, improvement of immunoprophylactics and use of biotechnological tools in evolving vaccines against important diseases of livestock and poultry. Efforts are to be made towards human resource development especially preparing specialists in frontier areas of research and sharpening the skills in latesttechniques through continuing education.